PER3 Polymorphism Predicts Cumulative Sleep Homeostatic but Not Neurobehavioral Changes to Chronic Partial Sleep Deprivation - Goel, Namni; Banks, Siobhan; Mignot, Emmanuel; Dinges, David F. (PloS one, 2009)
The variable number tandem repeat (VNTR) polymorphism 5-repeat allele of the circadian gene PERIOD3 (PER3(5/5)) has been associated with cognitive decline at a specific circadian phase in response to a night of total sleep deprivation (TSD), relative to the 4-repeat allele (PER3(4/4)). PER3(5/5) has also been related to higher sleep homeostasis, which is thought to underlie this cognitive vulnerability. To date, no study has used a candidate gene approach to investigate the response to chronic partial sleep deprivation (PSD), a condition distinct from TSD and one commonly experienced by millions of people on a daily and persistent basis. We evaluated whether the PER3 VNTR polymorphism contributed to cumulative neurobehavioral deficits and sleep homeostatic responses during PSD. PER3(5/5) (n = 14), PER3(4/5) (n = 63) and PER3(4/4) (n = 52) healthy adults (aged 22-45 y) demonstrated large, but equivalent cumulative decreases in cognitive performance and physiological alertness, and cumulative increases in sleepiness across 5 nights of sleep restricted to 4 h per night. Such effects were accompanied by increasing daily inter-subject variability in all groups. The PER3 genotypes did not differ significantly at baseline in habitual sleep, physiological sleep structure, circadian phase, physiological sleepiness, cognitive performance, or subjective sleepiness, although during PSD, PER3(5/5) subjects had slightly but reliably elevated sleep homeostatic pressure as measured physiologically by EEG slow-wave energy in non-rapid eye movement sleep compared with PER3(4/4) subjects. PER3 genotypic and allelic frequencies did not differ significantly between Caucasians and African Americans. The PER3 VNTR polymorphism was not associated with individual differences in neurobehavioral responses to PSD, although it was related to one marker of sleep homoeostatic response during PSD. The comparability of PER3 genotypes at baseline and their equivalent inter-individual vulnerability to sleep restriction indicate that PER3 does not contribute to the neurobehavioral effects of chronic sleep loss.